2003
DOI: 10.1046/j.1526-4610.2003.03164.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes During Migraine Attacks

Abstract: We conclude that ECG abnormalities often are present during a migraine attack, and for most of these, particularly PR and corrected QT interval lengthening, these abnormalities will be absent or less prominent during pain-free intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
(86 reference statements)
0
30
0
Order By: Relevance
“…This is in contrast with the literature in adults, which illustrates a variety of other conduction and rhythm issues during migraine headache, such as sinus bradycardia, premature ventricular beats, right bundle branch block, nonspecific ST-T wave abnormalities, 8 and prolongation of the PR interval. 9 This could be related to the prevalence of ischemic heart disease and other cardiac comorbidities in the adult population. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with the literature in adults, which illustrates a variety of other conduction and rhythm issues during migraine headache, such as sinus bradycardia, premature ventricular beats, right bundle branch block, nonspecific ST-T wave abnormalities, 8 and prolongation of the PR interval. 9 This could be related to the prevalence of ischemic heart disease and other cardiac comorbidities in the adult population. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study comparing ECGs during acute migraine to those obtained when the patients were pain-free, illustrated sinus bradycardia, prszemature ventricular beats, right bundle branch block, and nonspecific ST segment and T wave abnormalities during headaches. 8 Aygun et al 9 reported that 30% of migraineurs developed arrhythmia in association with migraine attacks and significant prolongation of PR and QTc intervals . Similarly, Duru et al 10 reported increased QTc intervals, QTc dispersion, and P-wave dispersion during acute migraine.…”
mentioning
confidence: 99%
“…In our study, we found that P max and P min were similar between migraine patients and controls. Similarly, Aygun et al reported that ECG abnormalities particularly PR and corrected QT (QTc) interval lengthening often were present during a migraine attack, and these abnormalities would be absent or less prominent during pain-free intervals [22]. Duru et al also found that ECG abnormalities including P -wave dispersion were more prominent during migraine attack [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ECG changes have been described in migraine. A study by Aygun et al (11) demonstrated T‐wave changes in 66% of patients during the phase of a migraine attack which became absent or less prominent during pain‐free intervals.…”
Section: Discussionmentioning
confidence: 99%